Patterns of morphological diversification are influenced by dietary evolution in a highly species-rich lizard radiation - Ocampo, Mauricio; Pincheira-Donoso, Daniel; Rios, Rodrigo S. (Frontiers in Ecology and Evolution, 2024)
The diversification of lineages is facilitated or constrained by the simultaneous evolution of multiple components of the phenotype that interact with each other during the course of speciation. When evolutionary radiations are adaptive, lineages proliferate via the emergence of multiple phenotypic optima that underlie diversification of species across multiple ecological niches. When radiations are non-adaptive, lineage proliferation unfolds constrained by similar (or nearly identical) correlations among traits that keep phenotypic and ecological diversity across species within a single optimum. Nature offers very few opportunities where both types of diversification occur between closely related and highly diverse lineages. The Liolaemidae family of South American lizards offers unique such opportunities given two speciose lineages that have rapidly proliferated via adaptive (Liolaemus) and non-adaptive (Phymaturus) radiations. Here, we analyze body shape in lizards in association with type of diet (herbivory, omnivory or carnivory). In these lizards, diet types have been suggested to be linked to body size. Our results confirm this hypothesis, with three body size optima tightly linked to all three diet types when radiation is both adaptive and non-adaptive. Diet reconstruction along their evolutionary history showed that the common ancestor of Liolaemidae was likely omnivorous, which is matched by ancestral reconstruction of body size. Phylogenetic PCA revealed that herbivorous species generally have more differentiated body shape than insectivores and omnivores. Herbivorous species have evolved larger heads, shorter hindlimbs and a small difference between forelimb and hindlimb length. In contrast, omnivores and insectivores have smaller heads and longer hindlimbs. Collectively, trophic niche plays an important role in defining body shape and size across species within lineages, and the patterns of trait-ecology correlations remain consistent when lineages have diversified via adaptive and non-adaptive radiation.